2006
DOI: 10.2495/dn060021
|View full text |Cite
|
Sign up to set email alerts
|

A graphic way for notch shape optimization

Abstract: Many components have notches and notches are in the majority of cases the reason for failure. There are many options to reach a longer lifetime and a better utilisation of material. One method for the shape optimization of components, developed in Forschungszentrum Karlsruhe, uses the design rules of nature. During the last 15 years it has spread very well and proven itself in industry, especially in automotive engineering. The limits for using the CAO-method (Computer Aided Optimization) are more or less of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A large quantity of waste placed in landfills comes from construction and demolition sites, and its toxicity can contaminate the environment, including ground water [ 2 , 3 ]. Various studies have shown that children from various countries, such as USA, Nigeria, and France, are being poisoned with lead from buildings, especially through paint degrading into dust particles [ 69 , 70 , 71 , 72 , 73 , 74 ]. As a response, various fungal species can serve to substantially reduce lead concentration in aqueous substrates [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large quantity of waste placed in landfills comes from construction and demolition sites, and its toxicity can contaminate the environment, including ground water [ 2 , 3 ]. Various studies have shown that children from various countries, such as USA, Nigeria, and France, are being poisoned with lead from buildings, especially through paint degrading into dust particles [ 69 , 70 , 71 , 72 , 73 , 74 ]. As a response, various fungal species can serve to substantially reduce lead concentration in aqueous substrates [ 75 ].…”
Section: Discussionmentioning
confidence: 99%